(untitled) (Conversatoria Linguistica, 2019)
The main focus of the article is the methodology of developing and saving sounds in the treatment of children with peripheral dyslalia. The therapeutic techniques subjected to the experiment were divided for the purpose of the research conducted into two groups of methods, referred to as interfering and non-interfering here. The main criterion for such a division was the patient’s tactile stimulation or its lack. The theoretical aim of the conducted experiment was the exploration of the impact of the interfering and non-interfering methods on the correction of articulation skills in preschool children. The research was also supposed to answer the question of whether providing more sensory stimuli (tactile, sensory) affects the effectiveness of the therapy of speech defects.